2010
DOI: 10.1002/rob.20333
|View full text |Cite
|
Sign up to set email alerts
|

Modeling, experimenting, and improving skid steering on a 6 × 6 all‐terrain mobile platform

Abstract: Multiple-wheel all-terrain vehicles without a steering system must use great amounts of power when skid steering. Skid steering is modeled with emphasis put on the ground contact forces of the wheels according to the mass distribution of the vehicle. To increase steering efficiency, it is possible to modify the distribution of the normal contact forces on the wheels. This paper focuses on two aspects: first, it provides a model and an experimental study of skid steering on an all-road 6×6 electric wheelchair, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…If the direct yaw moment is implemented on the vehicle, its dynamic characteristic must be changed. Otherwise, when the effect of hydraulic steering method is reduced actively (such as reducing the pressure of accumulator, which influence the pressure of hydraulic struts directly), the appropriate additional yaw moment can be obtained from equation (17) to keep the vehicle in reasonable steering process. Correspondingly, the vehicle can reduce the dependency of the steering process on the hydraulic steering method, which is the principle of assist-steering method in this paper.…”
Section: Researches On Assist-steering Methods For Dahvsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the direct yaw moment is implemented on the vehicle, its dynamic characteristic must be changed. Otherwise, when the effect of hydraulic steering method is reduced actively (such as reducing the pressure of accumulator, which influence the pressure of hydraulic struts directly), the appropriate additional yaw moment can be obtained from equation (17) to keep the vehicle in reasonable steering process. Correspondingly, the vehicle can reduce the dependency of the steering process on the hydraulic steering method, which is the principle of assist-steering method in this paper.…”
Section: Researches On Assist-steering Methods For Dahvsmentioning
confidence: 99%
“…Skid steering is widely used in tracked vehicles, skid-steer loaders, all-terrain vehicles, and industrial robots. [16][17][18][19] Its control methods are mostly based on the steering theory of tracked vehicles. But, compared to DAHVs, its structure and steering process are much different.…”
Section: Introductionmentioning
confidence: 99%
“…Kang and colleagues 1416 and Yan et al 17 created a cost function considering the friction circle through the estimation of longitudinal and vertical tire force. As Faurous and Vaslin 18 modeled the skid-steering vehicle with emphasis on the ground contact force with wheels and concluded that the normal force distribution of the vehicle is efficient to increase the steering performance, Zhao et al 19 considered the vertical load dynamics to reduce the vertical load transfer. Nah et al 20 presented a torque distribution strategy to balance the allocation error and the actuation cost to improve the vehicle maneuverability.…”
Section: Introductionmentioning
confidence: 99%
“…Soodhana 22 used the software ADAMS to construct a dynamic model, and the transient response was analysed in the step differential torque input condition. Fauroux 23 analysed the influence of the suspension stiffness on the torque demand in the cornering condition, and the mechanical properties of the tyres were expressed by a typical test curve which indicates the relationship between the lateral slip angle and the lateral force. Maclaurin 24 compared the steering performance of a skid-steered vehicle with that of a similar Ackermann steered vehicle, and the properties of the tyres were expressed by the 'magic formula'.…”
Section: Introductionmentioning
confidence: 99%